When a friend needs a friend - Roozeboos (Children's author) (New York : Scholastic Press, 2022)
When Oskar feels sad and wants to be alone his best friend Aya helps remind him of things he loved.
1.6
K-3
AD480L
Keywords: Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Best friends -- Fiction; Friendship -- Fiction